Estrategias metodológicas para mejorar la lectura comprensiva en el proceso enseñanza-aprendizaje en el bloque 5 del área de estudios sociales, de los niños y niñas del cuarto grado paralelo “B” del subnivel básica elemental de la escuela de educación general básica Julio María Matovelle del cantón y provincia de Loja. Año lectivo 2013–2014 - Ponce Ríos, Yadira Vanessa (2015)
The present investigation concerns: Methodological strategies to improve reading comprehension in the teaching-learning process in block 5 of the Department of Social Studies, children of the fourth parallel degree "B" elementary basic sublevel School General Basic Education Julio María Matovelle the canton and province of Loja. 2013-2014 school year; the same who worked with the following general objective: to propose methodological strategies for improving reading comprehension in the teaching-learning process in Block 5 of the Department of Social Studies of children parallel Fourth Grade "B" Sublevel Basic Elemental , School of Basic Education General Julio María Matovelle, canton and province of Loja. Academic year 2013 - 2014; it had a population of 30 people distributed between teacher and students, who helped clear the various concerns raised by applying instruments such as: the survey, pre-test and post-test, the observation guide and checklist; deductive, inductive, descriptive and statistical methods that helped to obtain scientific information was used. Among the findings I can point out that there are problems in reading comprehension and strategies used by the teacher are not enough to improve reading comprehension in students, so it was necessary to make a proposed solution, which consisted in raising workshops involving strategies such as: cartoon, wonder and cloze activities together with strategies animation, which allowed me to optimize the development of skills in students and improve reading comprehension